Titanium Mesh Exposure After Bone Grafting: Treatment Approaches-A Systematic Review - Cunha, Giovanni [UNESP]; Carvalho, Pedro Henrique de Azambuja [UNESP]; Quirino, Lilian Caldas [UNESP]; Torres, Luiz Henrique Soares [UNESP]; Filho, Valfrido Antonio Pereira [UNESP]; Gabrielli, Mario Francisco Real [UNESP]; Gabrielli, Marisa Aparecida Cabrini [UNESP] (Sage Publications Inc, 2021)
Study Design: A systematic review according to PRISMA statement has been designed to answer the preliminary question: In titanium mesh exposures, is there a treatment alternative which leads to an increased graft maintenance? and fill the PICO assessment out. Objective: To review studies published in the past 20 years (1999-2019) in which mesh exposure has occurred, detecting the suitable approaches to treat exposure allowing the graft maintenance. Methods: Initial search on PUBMED, SCOPUS, and COCHRANE databases resulted in 777 articles, and hand-searching identified 6 articles. After removing duplicates and unrelated articles, eligibility criteria were applied, and 31 studies were selected (randomized clinical trials, retrospective/prospective clinical trials, and case series). Results: A total of 677 surgical sites and 225 cases of mesh exposure were identified. Eleven treatments have been identified. Chlorhexidine was the primary approach in 46% of cases, followed by oral hygiene instructions and follow-up with 22.5% of occurrences. In 21% of clinical situations, titanium mesh removal was the treatment of choice, associated with other measures (i.e., antibiotic prescription). There seems to be a consensus in cases of infection. When this complication was associated with tissue dehiscence, the primary treatment was mesh removal. The same does not occur when the site needs to be cleaned for long-term periods. Conclusion: In 2 decades of use of titanium meshes, the available treatments do not seem to have evolved, and there is not enough data to establish a guideline.
Keywords: bone graft; chlorhexidine; dehiscence; exposure; titanium mesh